Evaluation of the Competitiveness of Business Activity in Tourist Enterprises - Umronov Eldorbek Sodirovich (European Science Publishing, 2023)
In the article, the following important situations affecting the competitiveness of these business entities are studied: different approaches to the assessment of business activity in tourist enterprises, evaluation of its struggle and analysis of the theory of competition. In the course of the research, the internal and external factors of competitiveness in the assessment of business activity in tourist enterprises approach to the assessment of competitiveness were formed and based on the author-based research.
Keywords: tourism, tourist services, competition, competitiveness, assessment, tourist activity, economic indicators, internal and external factors of competitiveness, small business and private entrepreneurship.